Kecemasan Sosial Pada Siswa Baru Di Sekolah Dasar Negeri 5 Limboto (Studi Kasus di SDN 5 Limboto Kab. Gorontalo) - Wahyuningsih Ponto; Samsi Pomalingo; Muhammad Sarlin; Nurainun; Sukri Katili (DE FACTO : Journal Of International Multidisciplinary Science, 2026)
This study aims to examine social anxiety among new students at SDN 5 Limboto, Gorontalo Regency. The study employed a qualitative approach with a case study design. Data were collected through observations, interviews, and documentation involving the school principal, two first-grade teachers, three parents, and three students. Data were analyzed using the Miles and Huberman interactive model with source triangulation. The findings indicate that students experienced fear of speaking in class, fear of making mistakes, difficulties interacting with peers, and difficulty separating from their parents. Most students were able to adapt to the school environment, while one student experienced persistent anxiety due to family separation and limited emotional support. The main factors contributing to social anxiety included parenting patterns, the school environment, family socioeconomic conditions, and students’ emotional experiences. These findings highlight the importance of teacher and parental support in helping students gradually adapt positively to the school environment from the beginning of elementary education.